Student Emotional Responses to Different Communication Situations - Rachel E Hendrix; Carley C Morrison (Journal of Applied Communications, 2020)
Communication and emotion are closely linked. Emotions experienced while communicating with others can affect one’s message both verbally and nonverbally. This study asked participants to identify the emotions they experienced when communicating with groups of different sizes. These emotions were drawn from, and displayed upon, the Circumplex Model of Affect, a figure developed by Posner, Russell, and Peterson (2005). This model divides 16 emotions into quadrants that lie along two axes: pleasantness and emotional arousal. Results show that as audience size increases, speakers’ emotions become more unpleasant, more highly aroused, and more variable overall. Prior research indicates that these negative emotions can have detrimental effects not just on the speaker’s message, but also on how the audience receives that message. Helping communicators understand the link between their emotions and their communication is a valuable step in improving communication ability and developing valuable emotional intelligence skills.
Keywords: Emotional Response; Communication Situations; Student Emotions